Upaya Guru Bk Membimbing Siswa Menggunakan Media Sosial dalam Proses Belajar di SMP Negeri 1 Padang Gelugur Pasaman Timur - Hasanah, Rahmayatul; Deswalantri, Deswalantri (Lembaga Yasin AlSys, 2023)
The purpose of this research is to find out what efforts are made by guidance and counseling teachers to guide students using social media in the learning process at SMP N 1 Padang Gelugur Pasaman Timur. The use of this research is to add insight into the efforts of guidance and counseling teachers to guide students using social media in the learning process. This research uses a qualitative approach that is descriptive. Collecting data in this study the authors obtained through observation and interviews. This study used 1 key informant, namely the guidance and counseling teacher and 3 supporting informants, namely students. Data collection techniques used are observation, interviews and documentation. Based on the results of the research, it can be understood that the efforts made by guidance and counseling teachers to guide students using social media in the learning process are preventive efforts, namely guidance and counseling teachers should provide information services carried out both individually and in groups, as well as supporting activities, namely in the form of case conferences. which is still not sufficient. Furthermore, namely curative efforts by providing individual counseling services, providing punishments that educate students, and collaborating with related parties, namely with school principals, student representatives, homeroom teachers, subject teachers and parents in guiding students using social media in the learning process. Then the next effort is a perservative effort by providing reinforcement in the form of praise and motivation to students